INTERNALISASI NILAI-NILAI PENDIDIKAN KARAKTER DILINGKUNGAN MADRASAH DAN SEKOLAH - Ansori (P3M IAI Nusantara Batang Hari, 2015)
Internalization of Values Character Education is a system of cultivation of character values to the resident of Madrasah and School, which includes knowledge, awareness or willpower, and actions to perform it, either against the Almighty God, ourselves, others, the environment, or nationality to become complete human beings.The values that need to be developed in Education Character in Madrasah and Schools is the peace, respect, compassion, tolerance, honesty, humility, cooperation, happiness, responsibility, simplicity, freedom and unity.The way that is done is always instilled by teachers to their students, by making posters that made the image that corresponds to the theme of the value above, along with a brief word that is easily understood by children or students at school. For example is